The compensatory enrichment of sphingosine-1-phosphate on HDL in FSGS enhances the protective function of glomerular endothelial cells compared to MCD - Yunfeng Xiong; Qiuping Ye; Lifang Liu; Wanjun Lin; Yonggen Liao; Ruiyu Gao; Jiaming Xu; Xinyu Zhang; Ruoyan Chen; Sihui Chen; Qiaoling Chen; Lixin Wei (Scientific Reports)
Abstract Glomerular endothelial cells (GECs) are pivotal in developing glomerular sclerosis disorders. The advancement of focal segmental glomerulosclerosis (FSGS) is intimately tied to disruptions in lipid metabolism. Sphingosine-1-phosphate (S1P), a molecule transported by high-density lipoproteins (HDL), exhibits protective effects on vascular endothelial cells by upregulating phosphorylated endothelial nitric oxide synthase (p-eNOS) and enhancing nitric oxide (NO) production. Nevertheless, the abundance of S1P within HDL in individuals with FSGS and minimal change disease (MCD) is yet to be elucidated, and its defensive role in GECs necessitates empirical confirmation. A total of 14 FSGS patients, 16 MCD patients, and 16 healthy controls (NC) were included in the study, with FSGS and MCD confirmed by renal biopsy. After blood sample collection, HDL was isolated and categorized into intact HDL, phospholipid-depleted HDL(apo-HDL), phospholipid-remained HDL(phoHDL), and recombinant HDL (rHDL). Various HDL samples, comprising intact, apo-HDL, pho-HDL and rHDL, were co-cultivated with human renal glomerular endothelial cells (HRGECs). Western blotting was utilized to quantify p-eNOS levels and assess PI3K-AKT pathway activation. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) analyzed S1P concentrations, while real-time quantitative PCR evaluated the expression of enzymes involved in S1P metabolism. Fluorescence labeling methods measured NO levels, and an immunofluorescence colocalization assay investigated Sphingosine-1-phosphate receptor 1 (S1PR1) expression in GECs across distinct kidney tissue groups. The HDL from FSGS patients demonstrated a significantly enhanced ability to promote p-eNOS expression and NO release in HRGECs compared to MCD patients and healthy controls. Additionally, the synthesis activity of S1P in renal tissues of FSGS patients was markedly higher than that observed in MCD patients and healthy controls, suggesting that S1P may play a crucial protective role in the progression of FSGS. Immunofluorescence staining showed that compared with MCD and NC, the expression of S1PR1 in GECs of FSGS patients was significantly decreased. Recombinant HDL with added S1P promoted the increase of p-eNOS in HRGECs. Knockdown of S1PR1 using siRNA reduced the expression of p-eNOS and NO release. The mechanism underlying the regulation of p-eNOS expression by rHDL was associated with the PI3K-AKT signaling pathway. The enhanced presence of S1P on HDL could serve as a diagnostic marker to differentiate FSGS from MCD. Incorporating S1P into HDL enhances glomerular endothelial cell function, suggesting that the S1P/S1PR pathway might offer a promising therapeutic avenue for FSGS.